LANDSLIDE SUSCEPTIBILITY MAPPING IN BERASTAGI DISTRICT KARO REGENCY BASED ON GEOGRAPHIC INFORMATION SYSTEMS - Desi Permata Sari; Nahor Manahat Simanungkalit; Nina Novira (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
This study aims to describe the spatial distribution of landslide prone areas in Berastagi District, Karo Regency with a Geographic Information System approach. Determination of the level of landslide susceptibility is obtained based on the method of scoring and weighting and overlaying of parameters including slope, rainfall, land use, soil type, rock type, and landform. The results showed that there were 4 levels of landslide susceptibility in Berastagi District, Karo Regency, namely low level of susceptibility 1,036.76 Ha (33.16%), medium level of susceptibility 772.02 Ha (24.69%), high level of susceptibility 1,055 .53 Ha (33.76 %), and very high level of susceptibility 262.13 Ha (8.38 %). The low level of susceptibility is dominated by Guru Singa Village (10.83 %), Raya Village (8.66 %), and Rumah Berastagi Village (3.72%). The medium and high level of susceptibility were dominated by Sempajaya Village at 4.51% and 3.68%. The very high level of susceptibility to landslides is dominated by Doulu Village, which is 17.40%. Meanwhile, the other 5 (five) villages have varying levels of susceptibility to landslides. Thus, 33.16% of the Berastagi District area is still safe from landslides, while the remaining 66.83% is prone to landslides.